Tindak Pidana Penyalahgunaan Wewenang oleh Aparatur Pengadilan Negeri: Analisis Normatif dan Reformulasi Sistem Pengawasan Peradilan - Ayu Putri Ramadhani; Musmulyadin Musmulyadin; Andriadin Andriadin (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2026)
This study aims to examine the criminal offense of abuse of authority committed by district court personnel and to analyze the framework of criminal liability within the Indonesian legal system. The research employs a normative legal research method using statutory, conceptual, and case approaches. Data were collected through library research, including legislation, court decisions, scholarly books, and peer-reviewed journal articles, and were analyzed using a descriptive-analytical method supported by legal interpretation and deductive reasoning. The findings reveal that abuse of authority within the judiciary is not limited to judges but may also be committed by court clerks, bailiffs, and other court personnel exercising judicial functions. Such conduct may constitute a criminal offense when it satisfies the legal elements prescribed by criminal law and therefore should not be addressed solely through ethical or administrative sanctions. The study highlights the need for an integrated framework of criminal accountability and judicial oversight to strengthen integrity, accountability, and legal certainty within Indonesia’s judicial system.